ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MAHASISWA PRODI PENDIDIKAN MATEMATIKA TERHADAP MATA KULIAH KEMUHAMMADIYAHAN - HADI, WINDIA; FARADILLAH, AYU (Jurnal Pendidikan Islam, 2018)
The purpose of this research is to analyze the ability of understanding concept among students in Mathematics Education Study Program to the course of keMuhammadiyahan. The indicators used in this study is to re-state a concept, to clarify the object according to certain traits in accordance with the concept, give examples and non examples, express the concept in various forms of representation. The method used in this research is a descriptive qualitative, where the researcher tries to describe the exposure analysis of the ability of concept comprehension based on the ability of understanding concept Mathematicsâ students. Based on the results obtained; one student has a good understanding of the concept in the re-state of a concept, one student has a good understanding of the concept in the example and non-example and one student has the ability to comprehend good concept in indicator express the concept in various forms of representation to the course kemuhammadiyahan.